DIVERSITAS SISTEM PENDIDIKAN DI FINLANDIA DAN RELEVANSINYA DENGAN SISTEM PENDIDIKAN DI INDONESIA - I Putu Suardipa (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2019)
Education urgency is the most profitable humanitarian investment and urgent for the nation's development. If you want to be in the field of education, Indonesia must want to have a number of countries that advanced in the field of education, as well as Finland. Finland has managed to make itself the country with the world's number one best education system. It is certainly not detached from the hard work and seriousness of the government to commit to the success of national education. There are several procedures in the education system in Finland that differ from other state education systems in the world. It should remain positioned that education is a social and humanitarian institution, not a political and business institution. The progress of a nation is more determined by the character of its inhabitants and the inhabitants are built through quality and relevant education. If a country or nation has advances in education, it can be ensured both socially, politically, and so on. But we need to know that the modern and advanced country will never be separated from education, because education is the center of the development of various aspects in a country.